PENGARUH RETURN ON ASSET (ROA) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - HJ. ERVIVA FARIANTIN (Universitas Mahasaraswati Mataram, 2019)
The research aims to analyze the influence of Return on Assets (ROA) and Net Profit Margin (NPM) partially and simultaneously on stock prices and the most dominant influence between Return On Asset (ROA) and Net Profit Margin (NPM) on stock prices in Pharmaceutical public companies listed on the Indonesia Stock Exchange in 2012-2017. The population in the study amounted to 10 companies with the sampling technique using purposive sampling so that the number of samples is 5 companies. The criteria in sampling are all Pharmaceutical public companies which issued a complete financial report for the period 2012-2017. The results show partially all independent variables (ROA and NPM) have an effect on stock prices, and simultaneously the independent variables (ROA and NPM) also have an effect on stock prices